2013
DOI: 10.1016/j.psyneuen.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in brain aromatase activity following sexual interactions in males: Where, when and why?

Abstract: Summary It is increasingly recognized that estrogens produce rapid and transient effects at many neural sites ultimately impacting physiological and behavioral endpoints. The ability of estrogens to acutely regulate cellular processes implies that their concentration should also be rapidly fine-tuned. Accordingly, rapid changes in the catalytic activity of aromatase, the limiting enzyme for estrogen synthesis, have been identified that could serve as a regulatory mechanism of local estrogen concentrations. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 48 publications
(72 reference statements)
7
57
1
1
Order By: Relevance
“…As previously observed in the entire HPOA, both types of interactions resulted in a rapid reduction of AA (56). The localisation of these changes depended, however, on the stimulus presented to the males.…”
Section: Short-term Regulation: In Vivo Studies -Effect Of Sexual Intsupporting
confidence: 77%
See 1 more Smart Citation
“…As previously observed in the entire HPOA, both types of interactions resulted in a rapid reduction of AA (56). The localisation of these changes depended, however, on the stimulus presented to the males.…”
Section: Short-term Regulation: In Vivo Studies -Effect Of Sexual Intsupporting
confidence: 77%
“…the female had been removed) (56). Interestingly, this experimental design did not reveal any alteration of the enzymatic activity, suggesting that the enzymatic decline may not depend on the short period of intense copulatory activity but rather on the female's presence that must last more than 2 min to be effective.…”
Section: Short-term Regulation: In Vivo Studies -Effect Of Sexual Intmentioning
confidence: 80%
“…Increasing evidence indicates that, particularly in the songbird, the concentration of brain androgens is acutely modulated through the regulation of their local synthesis (Pradhan et al, 2010;Heimovics et al, 2016). However, a rapid and reversible reduction in aromatase activity, paralleled by a change in estradiol brain concentration, was measured ex vivo in whole or specific hypothalamus/preoptic area subregions collected immediately after visual or sexual interactions with a female (Cornil et al, 2005;de Bournonville et al, 2013;Dickens et al, 2014), suggesting that aromatase activity is the critical component that determines estradiol availability. aromatase activity is upregulated in distinct brain regions following brief exposure to acute stress (Dickens et al, 2011), an effect that is counteracted by sexual interaction (Dickens et al, 2012).…”
Section: Neurotransmitter-like Effects Of Steroids Estrogens In Birdsmentioning
confidence: 99%
“…Rapid effects of estradiol on aggression have been identified in male mice (Trainor et al, 2008) and effects of aromatase inhibitors have been observed on aggression 24h after the treatment in non-breeding male song sparrows, Melospiza melodia (Soma et al, 2000). In parallel, aromatase activity (AA) in the preoptic area of male quail is decreased within minutes following sexual or visual interaction with the female (Cornil et al, 2005; de Bournonville et al, 2013). Interestingly, changes in AA and/or estradiol concentrations have been identified in different brain regions of males a few minutes after stress (Dickens et al, 2011; Dickens et al, 2014), aggressive interactions (Charlier et al, 2011) or hearing song (Remage-Healey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%